Early English Metre - Bredehoft, Thomas A. (Book collections on Project MUSE., 2005)
Early English Metre presents a new perspective on early English verse and a new perspective on much of early English literary history. It is an essential addition to the literature on Old and Middle English and will be widely discussed amongst scholars in the field.